## Trending News

Promoted

# F.2Maths!!!

7. Factorize the following expressions.

(a) 4n2(m − 8n) − 2n(8n − m) + 6mn(8n − m)

(b) ky(2k − h)(2x − 2y) − y(2k − h)2(x − y) + 2h(2h − 4k)(x − y)2

### 1 Answer

Rating

- Anonymous1 decade agoFavorite Answer
7. Factorize the following expressions.

(a) 4n2(m − 8n) − 2n(8n − m) + 6mn(8n − m)

= 4n^2 (m - 8n) - 2n (8n - m) (1-3m)

= 4n^2 (m - 8n) + 2n (m - 8n) (3m - 1)

= 2n (m - 8n) (2n + 3m -1)

(b) ky(2k − h)(2x − 2y) − y(2k − h)2(x − y) + 2h(2h − 4k)(x − y)2

= 2y (2k - h) (x - y) (k - 2k + h) + 4h (h - 2k) (x - y)^2

= 2 (x - y) [ y (2k - h) (k - 2k + h) + 2h (h - 2k) (x - y) ]

= 2 (x - y) [ y (2k - h) (h - k) - 2h (2k - h) (y - x) ]

= 2 (x - y) (2k - h) [ y (h - k) - 2h (y - x) ]

= 2 (x - y) (2k - h) ( hy - ky - 2hy + 2hx)

= 2 (x - y) (2k - h) [ 2hx - y ( h + k) ]

Still have questions? Get your answers by asking now.